Assistance to Strengthen Marketing Strategy During the Covid-19 Pandemic and Modernization of Dayak Ethnic Souvenir Products for UKM in Palangka Raya City - Meitiana; Liswara Neneng; Yusintha Tanduh (PT FORMOSA CENDEKIA GLOBAL, 2023)
The general objectives of the Community Entrepreneurial Lecturer Program (PDPWM) for Dayak Ethnic Souvenir Craftsmen UKM in Palangka Raya City, are: To provide insight and skills for Dayak ethnic Souvenir SMEs in marketing and producing quality souvenir products that are able to compete in local and international communities . The specific objectives of the Community Entrepreneur Assistant Lecturer Program (PDPWM) are: 1) Providing assistance in the form of improving marketing strategies for UKM Dayak Ethnic Souvenirs in Palangka Raya City; 2) Provide assistance for the modernization of Dayak Ethnic Souvenir products, so that they have more competitiveness in the market; 3) Increasing the variety of Dayak ethnic souvenir products through various models, and using various types of raw materials. The method of implementing service activities is carried out through 3 main activities, namely: 1) providing insight, 2) mentoring to improve skills, 3) evaluation of activities together. Several indicators of the success of this activity were measured from: 1) The number of variations of Dayak ethnic souvenir products produced by each group of craftsmen; 2) Number of variations in the use of various marketing strategies that have been mastered and used by each group of craftsmen.